2012
DOI: 10.1515/acv.2011.016
|View full text |Cite
|
Sign up to set email alerts
|

Lusin's condition and the distributional determinant for deformations with finite energy

Abstract: Based on a previous work by the authors on the modelling of cavitation and fracture in nonlinear elasticity, we give an alternative proof of a recent result by Csörnyei, Hencl and Malý on the regularity of the inverse of homeomorphisms in the Sobolev space W 1;n 1 . With this aim, we show that the notion of fracture surface introduced by the authors in their model corresponds precisely to the original notion of cavity surface in the cavitation models of Müller and Spector (1995) and Conti and De Lellis (2003).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
45
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 39 publications
(48 citation statements)
references
References 31 publications
2
45
0
1
Order By: Relevance
“…In the mathematical theory that has developed, hole-creating deformations are obtained as singular minimizers of the stored energy of the material, whenever sufficiently large tensile loads are applied to the body (see, e.g., the seminal work by Ball [4], the review paper by Horgan and Polignone [20], or the more recent works by Müller and Spector [28], Sivaloganathan and Spector [36], Conti and De Lellis [10], and Henao and Mora-Corral [16,17,18]).…”
Section: Introductionmentioning
confidence: 99%
“…In the mathematical theory that has developed, hole-creating deformations are obtained as singular minimizers of the stored energy of the material, whenever sufficiently large tensile loads are applied to the body (see, e.g., the seminal work by Ball [4], the review paper by Horgan and Polignone [20], or the more recent works by Müller and Spector [28], Sivaloganathan and Spector [36], Conti and De Lellis [10], and Henao and Mora-Corral [16,17,18]).…”
Section: Introductionmentioning
confidence: 99%
“…for example, is also a problem with lack of compactness. Indeed, for a deformation u ∈ W 1,2 ∩ L ∞ (Ω, R 3 ), E(u) = 0 implies that Det Du = det Du (see Proposition 7.1 in [21] [21]) such that u n ⇀ u in W 1,2 and Det Du = det Du + π 6 δ p − π 6 δ O for two points P, O in the domain they considered, hence E(u) = 0. This example corresponds to what is called a dipole phenomenon, in harmonic maps theory for example.…”
Section: Introductionmentioning
confidence: 99%
“…Using tools from geometric measure theory, they defined a concept of new surface created by the deformation, and showed that the corresponding energy due to cavitation or fracture was proportional to the area of the created surface. Moreover, using the work by Conti and De Lellis [14] to cover the critical exponent, they showed in [38] that, when restricted to Sobolev deformations (so that cavitation was permitted but fracture was not), the model turned out to be essentially equivalent to that of [51].…”
Section: Introductionmentioning
confidence: 99%